Hemato-biochemical Profile of Ostriches (Struthio Camelus) based on Gender and Age of Birds - umar, dr zaima; qureshi, anas sarwar; shahid, rehmatullah; deeba, farah (Journal of the Hellenic Veterinary Medical Society, 2022)
The present study was conducted to determine the hematobiochemical analysis of ostrich (Struthio camelus) with respect to gender and progressive age. A total of 40 apparently healthy ostriches of both genders and two progressive age groups; young one (1 year to 2.4 years: group A); and adult (2.5 years to 5 years: group B) in equal number were used in this study. Blood samples were collected from the wing vein of the ostriches maintained in one of the ostrich farms near the Gogra in Pakistan. For hematobiochemistry analysis, the serum samples were obtained by centrifugation @ 500g for ten minutes) of collected blood samples and kept in 1ml aliquots. The hematobiochemical parameters included total protein, glucose, urea, uric acid, creatinine, aspartate amino transferase, alanine aminotransferase, gamma Glutamyl transferase, lactic dehydrogenase, alkaline phosphatase, cholesterol, triglycerides, sodium, potassium, calcium, phosphorus and magnesium. The results showed a significant age-related difference (P<0.05) in all serum biochemical values, however, the non-significant difference (P<0.05) were observed in males and females within the same age group. The mean values of cholesterol, HDL-C, uric acid and creatinine were non-significant (P>0.05) between two age groups from immature to adult age and between the genders of the same age group. The statistical analysis explained that sodium (Na) and potassium (K) values were significantly (P<0.05) increased in immature than the adult ostriches. Keeping in view these findings, we may conclude that this preliminary study embarked on establishing a set of reference values in serum biochemistry of ostrich in Pakistan.